A Contribution to the study of ground beetles (Coleoptera: Carabidae) in the Western Rhodope Mts. (Bulgaria) - Teofilova, Teodora Marius (Journal of BioScience and Biotechnology, 2018)
The available information on the diversity of the ground beetle fauna in the region of the Western Rhodope Mts. was enriched. A total of 133 species were found, including 16 endemic (12% of all) and 5 relict species. Ten species were new for the studied area: Amara morio nivium, Badister bullatus, Harpalus caspius, Laemostenus janthinus, Microlestes apterus, Pterostichus leonisi, Syntomus obscuroguttatus, Tachyura quadrisignata, Trechus asiaticus, Tachys micros. Genera Badister and Tachys were reported for the first time from the Western Rhodopes. Faunistic contribution was made for a region researched in detail for the last in 2006. The results proved the predominantly mesophilous nature of the habitats due to the large percentage of forest territories. The life forms of the carabids showed the prevalence of the zoophages over the mixophytophages both in qualitative (67%: 33%) and in quantitative terms (85.5%: 14.5%).